2013
DOI: 10.1021/jf401763f
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Drinking Water Treatment Residuals as a Novel Chlorpyrifos Adsorbent

Abstract: Recent efforts have increasingly focused on the development of low-cost adsorbents for pesticide retention. In this work, the novel reuse of drinking water treatment residuals (WTRs), a nonhazardous ubiquitous byproduct, as an adsorbent for chlorpyrifos was investigated. Results showed that the kinetics and isothermal processes of chlorpyrifos sorption to WTRs were better described by a pseudo-second-order model and by the Freundlich equation, respectively. Moreover, compared with paddy soil and other document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…frog and sh. Zhao et al 7 has found that the residual of drinking water treatment material can effectively adsorb chlorpyrifos in water with respect to paddy soil, which contains iron, aluminium hydroxide minerals and humic materials. Chishti et al used microorganisms to degrade chlorpyrifos in water.…”
Section: Introductionmentioning
confidence: 99%
“…frog and sh. Zhao et al 7 has found that the residual of drinking water treatment material can effectively adsorb chlorpyrifos in water with respect to paddy soil, which contains iron, aluminium hydroxide minerals and humic materials. Chishti et al used microorganisms to degrade chlorpyrifos in water.…”
Section: Introductionmentioning
confidence: 99%
“…Besides P, the DWTRs used in this study were also found to have high adsorption capability for hydrogen sulfide and chlorpyrifos. The adsorption capacities for hydrogen sulfide were approximately 14e15 mg g À1 (Wang and Pei, 2012), and the affinity (log Koc) for chlorpyrifos were 4.76e4.90 (Zhao et al, 2013).…”
Section: Sample Collectionmentioning
confidence: 99%
“…In fact, the DWTRs have been demonstrated non-hazardous according to the toxicity characteristic leaching procedure assessment method used by the US Environmental Protection Agency (Wang et al, 2014a). The DWTRs are amorphousness, have a high specific surface area, and also have a strong adsorption capability for many contaminants, e.g., phosphorus (P) (Makris et al, 2005b;Oliver et al, 2011), hydrogen sulfide (Wang and Pei, 2012), perchloric acid (Makris et al, 2006a), arsenic (Makris et al, 2006b;Gibbons and Gagnon, 2011), chromium (Zhou and Haynes, 2011), lead (Zhou and Haynes, 2011;Putra and Tanaka, 2011), mercury (Hovsepyan and Bonzongo, 2009), and selenium (Ippolito et al, 2009), as well as organic pollutants (Zhao et al, 2013;Punamiya et al, 2013). Based on these attributes, DWTRs have also been used for environment remediation, typically for P pollution control.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained correlation coefficients (R 2 ) were within the range of 0.91-0.99. Glyphosate sorption isotherms for TJ and SD soils with and without Fe/Al WTR amendment are of type L (n < 1), implying that glyphosate sorption sites will decrease with increasing glyphosate sorption Zhao et al (2013). b pH determined in aqueous slurry with soil/water ratio of 1:2.5. and the gradual saturation of potential sorption sites (Giles et al, 1960).…”
Section: Glyphosate Sorption By Wtr-amended Soilsmentioning
confidence: 99%